UPAYA PENCEGAHAN DAN PENANGANAN STUNTING MELALUI EDUKASI MENGGUNAKAN LEAFLET PADA MASYARAKAT DI DESA TUNGKARAN KECAMATAN MARTAPURA - Muhammad Ikhwan Rizki; Anna Khumaira Sari; Normaidah; Hayatun Izma; Liling Triyasmono; Laura Sarwo; Mutia Mawaddah; Sofia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Stunting is a condition of chronic malnutrition and has long-term impacts on growth, mental and cognitive abilities, low immunity, productivity and reproduction. Tungkaran Village is in Banjar Regency, South Kalimantan. The prevalence of stunting under five cases in South Kalimantan in 2018 reached 25-30%. The lecture method is a method of conveying information orally. Leaflets are printed media for conveying information to the public effectively. The aim of this activity is to increase public knowledge as an effort to prevent and handle stunting incidents. Community service activities include stunting education to the community, pretests, delivering education using leaflets, discussions and questions and answers, as well as evaluating activities with posttests. The results of implementing community service in Tungkaran Village, Martapura District, Banjar Regency using the lecture method using leaflet media showed an increase in the knowledge of mothers of toddlers, posyandu cadres and the community about preventing and handling stunting in children from 77.57% to 99.69%.